2019
DOI: 10.1002/jmv.25644
|View full text |Cite|
|
Sign up to set email alerts
|

Significance of switching of the nucleos(t)ide analog used to treat Japanese patients with chronic hepatitis B virus infection from entecavir to tenofovir alafenamide fumarate

Abstract: The significance of switching of the nucleos(t)ide analog used to treat patients with hepatitis B virus (HBV) from entecavir (ETV) to tenofovir alafenamide fumarate (TAF) is uncertain. The subjects of this study were 159 patients with HBV who received treatment with ETV followed by TAF. Among these patients, serial changes in the HBV marker levels were monitored in 92 patients in whom the serum HBsAg levels were ≥100 IU/mL during the 48-week period immediately before and after the switching. A questionnaire su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Controversy exists, however, as to whether TAF exerts superior efficacy to ETV in reducing the serum HBsAg level [16][17][18][19][20][21]. Kumada T, et al reported results similar to ours [11] in patients in whom the nucleos(t)ide analog used for treatment was switched from ETV to TAF [16]; on the other hand, Ogawa E, et al [17] did not find any superiority of TAF over ETV, in terms of the efficacy of the drugs in reducing the serum HBsAg levels. Moreover, Hagiwara et al reported similar degrees of reduction of the serum HBsAg level between patients in whom the nucleos(t)de analog was switched from ETV to TAF and those who had received ETV monotherapy [18,19].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Controversy exists, however, as to whether TAF exerts superior efficacy to ETV in reducing the serum HBsAg level [16][17][18][19][20][21]. Kumada T, et al reported results similar to ours [11] in patients in whom the nucleos(t)ide analog used for treatment was switched from ETV to TAF [16]; on the other hand, Ogawa E, et al [17] did not find any superiority of TAF over ETV, in terms of the efficacy of the drugs in reducing the serum HBsAg levels. Moreover, Hagiwara et al reported similar degrees of reduction of the serum HBsAg level between patients in whom the nucleos(t)de analog was switched from ETV to TAF and those who had received ETV monotherapy [18,19].…”
Section: Discussionsupporting
confidence: 66%
“…In our previous study, in which the extent of reduction of the serum HBsAg level between the 48-week periods before and after switching of the nucleos(t)ide analog used for treatment from ETV to TAF were compared in 92 patients with chronic HBV infection, the extent of reduction, overall, was greater during the 48-week TAF treatment period after the drug switching than during the 48-week ETV treatment period prior to the drug switching (Log IU/mL; 0.068 vs. 0.041), although the difference was not significant (P = 0.069); the extent of reduction during the TAF treatment period was, however, significantly greater in patients without underlying cirrhosis, patients with genotype B HBV infection, and patients with serum HBcrAg levels of <3.0 Log U/mL [11]. Moreover, the McNemar test revealed that the antiviral efficacy of TAF was superior to that of ETV when increase and decrease of the serum HBsAg level by 0.08 Log IU/mL/48 weeks or more were defined as "increase" and "decrease," respectively (P = 0.022) [11]. Controversy exists, however, as to whether TAF exerts superior efficacy to ETV in reducing the serum HBsAg level [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Hagiwara, et al reported that it was particularly prominent in patients with serum HBs antigen levels < 800 IU/mL after switching from ETV to TAF [36]. Uchida et al found that the degree of reduction in serum HBs antigen levels after switching from ETV to TAF was significantly higher, particularly in patients with cirrhosis, genotype B HBV infection, and serum hepatitis B core related antigen levels <3.0 log U/mL [37].…”
Section: Efficacy and Safety Of Tafmentioning
confidence: 99%